Standardizing protocols for determining the cause of mortality in wildlife studies. Issue 6 (23rd June 2022) - Cristescu, Bogdan; Elbroch, L. Mark; Forrester, Tavis D.; Allen, Maximilian L.; Spitz, Derek B.; Wilmers, Christopher C.; Wittmer, Heiko U.
Abstract: Mortality site investigations of telemetered wildlife are important for cause‐specific survival analyses and understanding underlying causes of observed population dynamics. Yet, eroding ecoliteracy and a lack of quality control in data collection can lead researchers to make incorrect conclusions, which may negatively impact management decisions for wildlife populations. We reviewed a random sample of 50 peer‐reviewed studies published between 2000 and 2019 on survival and cause‐specific mortality of ungulates monitored with telemetry devices. This concise review revealed extensive variation in reporting of field procedures, with many studies omitting critical information for the cause of mortality inference. Field protocols used to investigate mortality sites and ascertain the cause of mortality are often minimally described and frequently fail to address how investigators dealt with uncertainty. We outline a step‐by‐step procedure for mortality site investigations of telemetered ungulates, including evidence that should be documented in the field. Specifically, we highlight data that can be useful to differentiate predation from scavenging and more conclusively identify the predator species that killed the ungulate. We also outline how uncertainty in identifying the cause of mortality could be acknowledged and reported. We demonstrate the importance of rigorous protocols and prompt site investigations using data from our 5‐year study on survival and cause‐specific mortality of telemetered mule deer ( Odocoileus hemionus ) in northern California. Over the course of our study, we visited mortality sites of neonates ( n  = 91) and adults ( n  = 23) to ascertain the cause of mortality. Rapid site visitations significantly improved the successful identification of the cause of mortality and confidence levels for neonates. We discuss the need for rigorous and standardized protocols that include measures of confidence for mortality site investigations. We invite reviewers and journal editors to encourage authors to provide supportive information associated with the identification of causes of mortality, including uncertainty. Abstract : ‐ Mortality site investigations provide critical data for population ecology, but the complexities of field investigations and confounding factors can affect replicability, and potentially lead to unreliable conclusions and management recommendations. ‐ We elaborate on common problems and on how sampling methods can be improved, summarize essential information to be recorded, and introduce a simple means to account for uncertainty in a decision tree approach. ‐ We illustrate our points with data from an intensive study on ungulate survival in California, in a system with multiple carnivores.